Comparison between ticlopidine and clopidogrel in patients with ST-segment elevation myocardial infarction treated with coronary stenting - De Luca, Giuseppe; Suryapranata, Harry; van’t Hof, Arnoud W. J.; Ottervanger, Jan Paul; Hoorntje, Jan C. A.; Gosselink, A.T. Marcel; Dambrink, Jan-Henk E.; Zijlstra, Felix; de Boer, Menko-Jan (Thrombosis and Haemostasis, 2004)
Controversy still surrounds the question, which antiplatelet drug should be added to aspirin in patients undergoing coronary stent implantation. The aim of the current study was to compare ticlopidine and clopidogrel in a consecutive series of patients with ST-segment elevation myocardial infarction (STEMI) treated with primary stenting. Our population is represented by 883 consecutive patients with STEMI undergoing primary stenting from April 1997 to October 2001. All clinical, angiographic, and follow-up data were prospectively collected. A total of 523 patients on clopidogrel were compared with 360 patients on ticlopidine after primary stenting. Except for age and statin therapy, no difference in demographic and clinical characteristics was observed between the two groups. Patients on clopidogrel had a higher rate of successful reperfusion (80.7% vs 73.1%, p = 0.008). No difference was observed between the two groups at both 30-day and 1-year follow-up. These data were confirmed after correction for age, successful reperfusion and statin therapy. This study shows no difference in long-term clinical outcome between clopidogrel and ticlopidine as adjunctive antiplatelet therapy in patients with STEMI undergoing stent implantation.
Keywords: Antiplatelet therapy; stenting; primary angioplasty; outcome